Establishing statistical confidence in Cortex Ratios within and among lithic assemblages: a case study of the Middle Paleolithic of southwestern France. (July 2015) - Lin, Sam C.; McPherron, Shannon P.; Dibble, Harold L.
Abstract: Recent studies have demonstrated the usefulness of the Cortex Ratio for quantifying the cortex composition in lithic assemblages and as a viable index of prehistoric artifact transport. Yet, the lack of means for assigning statistical confidence to archaeologically observed Cortex Ratios inhibits the approach's utility for objective comparisons and interpretation. Here, we derive statistical confidence for archaeological Cortex Ratios through Monte Carlo and resampling techniques. Experimental data with known geometric properties and measured cortex values were employed as a reference for attaching a probability to an archaeological assemblage's Cortex Ratio. The method is demonstrated on assemblages from the Middle Paleolithic sites of Roc de Marsal, Pech de l'Azé IV, and Combe-Capelle Bas in southwestern France. Highlights: Cortex Ratio is a measure of lithic assemblage cortex composition. Statistical confidence is established between archaeological Cortex Ratios. Monte Carlo sampling allows quantitative comparisons between different ratio values. Middle Paleolithic Cortex Ratios show changing patterns in the late Pleistocene. Results have implications for the interpretation of Cortex Ratio and lithic transport.